You are on page 1of 8

# 1

Assignment 2 — Solutions 1/23/04 (revised 2/2/2004)
Problem 1.17
(a)

From equation 1.54:

e0
÷” 2
W = ÅÅÅÅÅÅÅÅ ‡ °“ F• 3 x
2

In the language of equation 1.62, we're given Vi = 0 for i ∫ 1, V1 = 1, C11 ª C . So
1 n n
1
1
e0
÷” 2
÷” 2
W = ÅÅÅÅÅ ‚ ‚ Ci j Vi V j = ÅÅÅÅÅ C11 = ÅÅÅÅÅ C = ÅÅÅÅÅÅÅÅ ‡ °“ F• 3 x ï C = e0 ‡ °“ F• 3 x
2 i=1 j=1
2
2
2

(b)
Let F be the true potential. We can write Y = F + dY , where dY is arbitrary except that Y must satisfy the same
boundary conditions as F. This implies that dY must vanish on the boundaries, which we will use below:
÷” 2
C@YD ª e0 ‡ °“ Y• 3 x

÷”
÷”
÷” ÷”
C@YD - C@FD = e0 ‡ “ HF + dYL ÿ “ HF + dYL 3 x - e0 ‡ “ F ÿ “ F 3 x
V

÷” ÷”
÷”
÷”
= e0 ‡ A2 “ F ÿ “ HdYL + “ HdYL ÿ “ HdYLE 3 x
V

V

V

From Green's first identity:
∑F
÷”
÷”
2
3
‡ AdY “ F + “ HdYL ÿ “ FE  x = ® dY ÅÅÅÅÅÅÅÅÅÅ a = 0 since dY§S = 0
∑n
V
S

The true potential must satisfy “2 F = 0 within V , so

÷”
÷”
2
2
C@YD - C@FD = -2 e0 ‡ dY “2 F 3 x + e0 ‡ °“ HdYL• 3 x = e0 ‡ °“ HdYL• 3 x ¥ 0
V

V

V

Hence we have shown that C@YD ¥ C@FD, where C@FD is the true capacitance.

Problem 1.22
(a)

2
ƒƒƒ
ƒƒ
1 ij ∑
∑ yzn
£
£
FHx, yL = „ ÅÅÅÅÅÅÅÅ jx ÅÅÅÅÅÅÅÅÅÅÅÅ + y ÅÅÅÅÅÅÅÅÅÅÅÅ z FHx , y L§ƒ
£
£
ƒƒƒ
n! k ∑ x
∑y {
ƒƒx£ =0=y£
n=0
Sc = FHh, 0L + FH0, hL + FH-h, 0L + FH0, -hL

ƒƒƒ
ƒƒ
1 ÅÄÅÅi ∑ yn ij ∑ yzn i
∑ yn ij
∑ yzn ÑÉÑÑ
= „ ÅÅÅÅÅÅÅÅ ÅÅÅjjh ÅÅÅÅÅÅÅÅÅÅÅÅ zz + jh ÅÅÅÅÅÅÅÅÅÅÅÅ z + jj-h ÅÅÅÅÅÅÅÅÅÅÅÅ zz + j-h ÅÅÅÅÅÅÅÅÅÅÅÅ z ÑÑÑ FHx£ , y£ L§ƒ
ƒƒƒ
n! ÅÅÇk ∑ x£ {
∑ x£ {
∑ y£ { ÑÖÑ
k
k ∑ y£ {
k
ƒƒx£ =0=y£
n=0
ƒƒƒ

ƒƒ
ÅÄÅ ∑n
1
∑n ÑÉÑ
= „ ÅÅÅÅÅÅÅÅ @1 + H-1Ln D hn ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ FHx£ , y£ L§ƒ
ÅÅÇ ∑ x£n
ƒƒƒ
n!
∑ y£n ÑÑÖ
ƒƒ £
£
n=0

x =0=y

Clearly all the n odd terms vanish, and all the n even ones have a a numerical factor of 2 ê n!. Immediately we see
É
É
ƒƒƒ
ƒƒƒ
ÅÄÅ ∑2
ÅÄÅ ∑4
2
2
∑2 ÑÑÑ
2
∑4 ÑÑÑ
Å
Å
Sc = ÅÅÅÅÅÅÅÅ @1 + 1D FH0, 0L + ÅÅÅÅÅÅÅÅ h2 ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ FHx£ , y£ L§ƒ + ÅÅÅÅÅÅÅÅ h4 ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ FHx£ , y£ L§ƒ + Ih6 M
ÅÅÇ ∑ x£2
ÅÅÇ ∑ x£4
ƒƒ0 4!
ƒƒ
0!
2!
∑ y£2 ÑÑÖ
∑ y£4 ÑÑÖ
0
ƒƒƒ
h4
2
2
6
= 4 FH0, 0L + h “ F•0 + ÅÅÅÅÅÅÅÅÅ HFxxxx + F yyyy L§ƒ + Ih M
ƒƒ0
12

(b)
ƒƒƒ
ƒƒ
1 ÄÅÅÅji ∑

∑ yzn ji
∑ yzn ji
∑ yzn ji ∑
∑ yzn ÉÑÑÑ
£
£
= „ ÅÅÅÅÅÅÅÅ ÅÅÅjh ÅÅÅÅÅÅÅÅÅÅÅÅ + h ÅÅÅÅÅÅÅÅÅÅÅÅ z + j-h ÅÅÅÅÅÅÅÅÅÅÅÅ + h ÅÅÅÅÅÅÅÅÅÅÅÅ z + j-h ÅÅÅÅÅÅÅÅÅÅÅÅ - h ÅÅÅÅÅÅÅÅÅÅÅÅ z + jh ÅÅÅÅÅÅÅÅÅÅÅÅ - h ÅÅÅÅÅÅÅÅÅÅÅÅ z ÑÑÑ FHx , y L§ƒ
£
£
£
£
£
£
£
£
Å
Ñ
ƒƒƒ
n! ÅÇk ∑ x
∑x
∑x
∑y {
∑y {
∑y {
∑ y { ÑÖ
k
k
k ∑x
ƒƒ0
n=0
ƒ

ƒƒƒ
ÄÅ ∑
ƒ
hn
∑ yn i ∑
∑ yn ÉÑÑ
Åi
= „ ÅÅÅÅÅÅÅÅÅ @1 - H-1Ln DÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz + jj- ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz ÑÑÑÑ FHx£ , y£ L§ƒ
£
£
£
£
Å
Ñ
ƒƒƒ
ÅÇk ∑ x
n!
∑y {
∑ y { ÑÖ
k ∑x
ƒƒ0
n=0
É
Ä
ƒƒƒ
2
2 h2 ÅÅÅi ∑
∑ y2 i ∑
∑ y2 ÑÑÑ
= ÅÅÅÅÅÅÅÅ @1 + 1D FH0, 0L + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz + jj- ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz ÑÑÑÑ FHx£ , y£ L§ƒ
ƒƒ0
0!
2! ÅÅÇk ∑ x£
∑ y£ {
∑ y£ { ÑÑÖ
k ∑ x£
Ä
É
ƒ
4
Å
Ñ
2 h ÅÅi ∑
∑ y4 i ∑
∑ y4 ÑÑ
ƒƒ
+ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz + jj- ÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ zz ÑÑÑÑ FHx£ , y£ L§ƒ + Ih6 M
£
£
£
£
ƒƒ
Å
Ñ
4! ÅÇk ∑ x
∑y {
∑ y { ÑÖ
k ∑x
0
Ä
ÄÅ 2
É
É ƒ
2 ÑÑ ƒƒƒ
4 ÅÅ
4
2
Å

∑2

h

∑4 ÑÑÑÑ ƒƒ
Å
Å
Ñ
2
Å
Å
Ñ
Å
Å
Ñ
= 4 FH0, 0L + 2 h ÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑ F ƒ§ + ÅÅÅÅÅÅÅÅÅ ÅÅ2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + 12 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + 2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑ F ƒ§ + Ih6 M
ÅÅÇ ∑ x£2
∑ y£2 ÑÑÖ ƒƒ0 12 ÅÅÇ ∑ x£4
∑ x£2 ∑ y£2
∑ y£4 ÑÑÖ ƒƒ0
ƒƒƒ
ÄÅ 4
ÉÑ ƒƒƒƒ
4
4
2
2
4

h
h ÅÅ ∑

∑ ÑÑ ƒ
= 4 FH0, 0L + 2 h2 “2 F•0 - ÅÅÅÅÅÅÅÅÅ 4 HFxxxx + F yyyy L + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + 2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ F §ƒ + Ih6 M
£2 ∑ y£2
ÅÅÇ ∑ x£4
12
2 ´¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨

x

y£4¨¨¨¨¨ÑÑÖÆ ƒƒƒ
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
¨¨¨¨¨¨¨¨≠¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
ƒƒƒ
2
2
“ “
ƒ0
ƒƒƒ
4
4
h
h
= 4 FH0, 0L + 2 h2 “2 F•0 - ÅÅÅÅÅÅÅÅÅ HFxxxx + F yyyy L + ÅÅÅÅÅÅÅÅÅ “2 “2 F §ƒ + Ih6 M
ƒƒ0
3
2

Sc = FHh, hL + FH-h, hL + FH-h, -hL + FHh, -hL

3

Problem 2.2
We could follow exactly the procedure in §2.2 and derive the answer. However since the work has been done for us,
let's just make an educated guess and then verify the answer. From equation 2.4 we see that with a point charge qè at yè
outside the sphere, we would need an image charge qè £ = -a qè ê yè at yè £ = a2 ê yè inside the sphere. As far as the potential
is concerned, it's moot as to which charge is real and which imaginary, so suppose we swap the roles. Let our system
have charge q = qè £ at y = yè £ inside the sphere, then the image charge should be q£ = qè at y£ = yè . Solving this:
y = a2 ë y£

ï y£ = a2 ë y ( ¥ a , which is good)

q = -a q£ ê y£ ï q£ = -q y£ ê a = -q a ê y

q ê 4 p e0
q£ ê 4 p e0
q ê 4 p e0
q Ha ê yL ê 4 p e0
q i 1
1
y
÷”L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ
Å
ÅÅÅ
Å
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅ
FHx
+
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
÷†x” - ÷y”§
÷†x” - ÅÅÅÅÅÅÅÅ
÷y”£ §ÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÅÅÅÅ
÷y”Å§ÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÷ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
”y a2 ê ÅÅÅÅÅÅÅÅ
÷

÷

÷

2
y §
4 p e0 k †x - y§
†x y ê a - ÷y” a ê y§ {

Go ahead and check the behavior if you want.
(b)

To take a derivative of a magnitude, with b and c” constants (though that's easy to generalize):

nê2

ÅÅÅÅÅÅÅÅÅ †b ÷x” - c”§n = ÅÅÅÅÅÅÅÅÅ @Hb ÷x” - c”L ÿ Hb ÷x” - c”LD
=
∑x
∑x
= n †b ÷x” - c”§n-2 Hb ÷x” - c”L ÿ Hb x` L =

ÄÅ ∑
ÉÑ
nê2-1
n
Å
Ñ
ÅÅÅÅÅ @Hb ÷x” - c”L ÿ Hb ÷x” - c”LD
2 Hb ÷x” - c”L ÿ ÅÅÅÅ ÅÅÅÅÅÅÅÅÅ Hb ÷x” - c”LÑÑÑÑ
Å
ÑÖ
2
Ç ∑x
÷

n-2
÷” - b•
n b °x
Hb x - c” ÿ x` L

The normal to the inner surface is -x` , so

∑F ƒƒ
q i x - ÷y” ÿ x`
Hy ê aL Hx y ê a - ÷y” ÿ x` a ê yL zy
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ zzz
ÅÅÅÅ
Å
ÅÅ
Å
= ÅÅÅÅÅÅÅÅÅÅ jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
+
s = +e0 ÅÅÅÅÅÅÅÅÅÅ §ƒ
÷” - ÷y”§3
÷” y ê a ÷y” a êÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
∑ x ƒx=a
4 p k †x
†x
y§3
{x=a
q a - y2 ê a
q ij
a - ÷y” ÿ x`
y2 ê a - ÷y” ÿ x` yz
q
a 1 - a2 ê y2
zz = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å
ÅÅÅ
Å
ÅÅÅ
Å
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å
ÅÅÅÅÅÅÅ
Å
ÅÅ
+
= ÅÅÅÅÅÅÅÅÅÅ jjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
z
4 p †a x` - y y` §3
4 p k †a x` - y y` §3
4 p a2 y †Ha ê yL x` - y` §3
†y x` - a y` §3 {

where the last expression is manifestly the negative of equation 2.5. It's fun to think why we should have expected this.
Suppose for a moment that both charges are real. Then if on the outer surface (of our spherical shell) a positive (say)
surface charge density has been induced, an opposite charge density must also be on the inner surface to keep the
sphere neutral. Why exactly the same distribution (up to sign)? You think on it.
(c)
We can use Coulomb's law to find that the image charge, which is opposite in charge, exerts an attractive force
÷”
on our charge, i.e. F is in the +r` direction. The magnitude is easy:
†q q£ §
1
q2 a ê y
1
q2
÷”
ÅÅÅÅÅÅÅÅ
Å
ÅÅÅÅÅÅÅ
Å
ÅÅÅ
Å
†F § = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ
Å
ÅÅÅ
Å
Å
=
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å
ÅÅ
Å
=
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅ
÷” - ÷y”£ §2
÷” - ÷y” a2 ê y2 §2
4 p e0 †y
4 p e0 †y
4 p e0 a2

a zy3 ij
jij ÅÅÅÅÅ
z jjj1 k y{ k

a2 y
ÅÅÅÅÅÅÅÅÅ zzzz
y2 {

-2

(d)
We can get the sphere to have potential V by superposing F with the potential F£ = V (duh). Simiarly we can
get it to have total charge Q by superposing with the potential F≥ = HQ - q£ L ê 4 p e0 †x” §. Clearly we don't need to do
anything to F. Refer to sections §2.3 and §2.4.

4

Problem 2.4
(a)

Taking ÷y” = d y` , a = R and Q = q in equation 2.9, we find the force on the charge to be
q R3 H2 d 2 - R2 L zy
1
q i
÷”
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz , F = F y`
F = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjjjq - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
2
2
4 p e0 d 2 k
d Hd - R L {

The force will be attractive if F < 0, i.e. dividing by q2 ê 4 p e0 d 2 > 0:
R3 H2 d 2 - R2 L
1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ < 0
d Hd 2 - R2 L2

Since d > R, we can write d = R + D for some D > 0. Then all the symbols that appear are positive:
R3 H2 R2 + 4 R D + 2 D2 - R2 L
R5 + 4 R4 D + 2 R3 D2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = 1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 0
HR + DL H4 R2 D2 + 4 R D3 + D4 L
HR + DL HR2 + 2 R D + D2 - R2 L2
R5 + 4 R4 D + 2 R3 D2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 1
4 R3 D2 + 8 R2 D3 + 5 R D4 + D5
R5 + 4 R4 D + 2 R3 D2 - 4 R3 D2 - 8 R2 D3 - 5 R D4 - D5 > 0

You can factor this in Mathematica, but otherwise we can try to guess. It's too hard (at least for yours truly) to see what
a root might be straight off, so let's try to factor out something bigger first. From the almost symmetrical roles of R 's
and D's we might guess R2 - D2 . Of course this is too easy, and taking one step to plug this in shows that it won't
work. The next term we could throw in would be something proportional to R D (there's no use trying to factor out
something that has mixed total powers, e.g. R2 + D ). So we do long division with R2 + R D - D2 and get something
like 22 R5 + 34 R4 D left over, which is no good either. Finally we try R2 - R D - D2 and it works (!). Sorry, there's no
formula for finding roots of quintics, you just have to do trial and error and get lucky. Anyway
IR2 - R D - D2 M IR3 + 5 R2 D + 4 R D2 + D3 M > 0

Since the second term is manifestly nonnegative, we need R2 - R D - D2 > 0. The roots are -I1 ≤

è!!!
5 M R ê 2, so

1
1
1
1
è!!!! y i
è!!!! y
è!!!! y i
è!!!! y
i
i
- jjD + ÅÅÅÅÅ I1 + 5 M Rzz jjD + ÅÅÅÅÅ I1 - 5 M Rzz > 0 = ï jjD + ÅÅÅÅÅ I1 + 5 M Rzz jjD + ÅÅÅÅÅ I1 - 5 M Rzz < 0
2
2
2
2
k
{k
{
k
{k
{
1
è!!!!
D + ÅÅÅÅÅ I1 - 5 M R < 0
2
1 è!!!!
D < ÅÅÅÅÅ I 5 - 1M R
2

(b)

Suppose the sphere has charge a q for some a > 0. Then
i
1
q2 i
q2
R3 H2 d 2 - R2 L y
R3 HR2 + 4 R D + 2 D2 L yz
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz
F = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjjja - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjjja - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4 p e0 HR + DL2 k
4 p e0 d 2 k
d Hd 2 - R2 L2 {
HR + DL H2 R D + D2 L2 {
a
1
q2 i
1 + 4 h + 2 h2 zy
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ jjjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz , h ª D ê R
2
2
4 p e0 R k H1 + hL
h2 H2 + hL2 H1 + hL3 {

5

Expand the second term in partial fractions:
1 + 4 h + 2 h2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
H1 + hL3 H2 + hL2 h2

=

A
B
C
ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
2
h
H2 + hL
H1 + hL3

1 + 4 h + 2 h2 = A H1 + hL3 H2 + hL2 + B H1 + hL3 h2 + C H2 + hL2 h2
h = 0 ï 1 = 4A
h = -1 ï -1 = C
h = -2 ï 1 = -4 B

a
q2 i
1
1
1
1
y
F = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
2
3
4 h2
4 p e0 R2 k H1 + hL2
4 H2 + hL
H1 + hL {

Evidently F Ø -¶ like -q2 ê 16 p e0 R2 h2 as h Ø 0 (remember that D is the distance from the surface of the sphere,
which the text calls a though I think that's confusing notation). Amazingly enough this holds for any a, i.e. it doesn't
matter what the sphere's charge is, as long as it's opposite in sign to that of the point charge.
(c)

Part (b) we've already done for general charge. For part (a) we'll have to solve the quintic
a
1 + 4 h + 2 h2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 0 ï a h5 + 5 a h4 + 8 a h3 + 2 H2 a - 1L h2 - 4 h - 1 > 0
2
2
H1 + hL
h H2 + hL2 H1 + hL3

which is generally untenable. Again, we can turn to the computer, but there is also a poor grad's way of guessing by
examining limiting cases and see which ones make sense. Since h = D ê R , we must have h ¥ 0 for a sensible result. We
also expect on physical grounds for D to be smaller for a = 2 and larger for a = 1 ê 2, with a = 1 around midway
between (roughly speaking, the amount of charge on the sphere is proportional to how strongly it can maintain a
repelling force). There are three cases:
First, suppose h ` 1, and drop terms of order h3 . Then
1
1
i
zyz jij
zyz
2 H2 a - 1L h2 - 4 h - 1 > 0 ó H2 - 4 aL jjjjh + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
! ÅÅÅÅÅÅÅÅÅÅ zz jjh - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
! ÅÅÅÅÅÅÅÅÅÅ zz > 0
è!!!!!!!!!!!!!!!!!!!!!
è!!!!!!!!!!!!!!!!!!!!!
2
H1
+
2
aL
+
2
2
H1
+
2
aL
2
k
{k
{

Actually, this could never hold for a = 2 where the h2 term vanishes and we're left with -4 h - 1 > 0 which cannot be
satisfied with positive h. That leaves the a = 2 case, where 2 - 4 a = -6 < 0 so (since the middle term on the last
expression must be positive) we need
1
1
h - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!! ÅÅÅÅÅÅÅÅÅÅÅÅ º 0.86 for a = 2
è!!!!!! ÅÅÅÅÅÅÅÅÅÅÅÅ < 0 ï h < ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
10 - 2
10 - 2

Taking h º 0.86 doesn't look good since it doesn't satisfy h ` 1. We can see how bad an error we made by plugging
this value into the quintic, which gives around 17. So we're lead to suspect that this is not the way to go.
As a second possibility suppose h º 1, i.e. h = 1 + ¶ for †¶§ ` 1. Plug this into the quintic and keep terms up to H¶2 L:
H18 a - 7L + H57 a - 8L ¶ + H68 a - 2L ¶2 > 0
è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
!!!!!!!!
!
!!
!
!!!!!!!!!!!!
ij
8 - 57 a + 8 + 1136 a - 1647 a2 yzz
8 - 57 a - 8 + 1136 a - 1647 a2 yzz ijj
H68 a - 2L jjjj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz jjj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz > 0
2 H68 a - 2L
2 H68 a - 2L
{k
{
k

6
è!!!!!!
è!!!!!!
è!!!!!!
ij
-41 + 3 73 yz
-41 + 3 73
41 + 3 73 yz ij
1
a = ÅÅÅÅÅ : 32 jjj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz jjj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz > 0 ï ¶ > ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º -0.12
2
128
128
128
{k
{
k

We can try applying this to a = 2, but the square root produces an imaginary number which is bad. Plugging in
h = 1 + ¶ º 1 - 0.12 = 0.88 for a = 1 ê 2 in the quintic gives -0.031, which is close enough for government work (yes,
it is negative, but if you let h be slightly more than 0.88 you will get a positive answer, which goes to show that we've
got it almost right).
Finally, we could repeat the whole process with h p 1, dropping positive powers of h smaller than h5 . But we know
that this cannot give us the right answer because as we've argued we should find for a = 2 a value less than the a = 1
case, which is around 0.62. Now we've tried h ` 1 and that didn't work, so the logical next guess would be h º 1 ê 2.
So let h = 1 ê 2 + ¶ for †¶§ ` 1, and repeat (this time I'll plug in a = 2 straight off since that's what we want):
19
157 ¶
95 ¶2
ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 0
16
8
2
95 i
1
1
è!!!!!!!!
!
!!!!
è!!!!!!!!
!
!!!!
y
i
y
ÅÅÅÅÅÅÅÅÅ jj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅ I157 + 10209 Mzz jj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 Mzz > 0
2 k
760
760
{k
{

1
è!!!!!!!!!!!!!
¶ > ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 M º -0.074
760

Plugging h = 1 ê 2 + ¶ º 1 ê 2 - 0.074 º 0.426 into the quintic gives -0.021, which is again very good agreement with
the provided answer of h º 0.428.
This is of course all just a fancy way of making educated guesses as to how to utilize Newton's method with a reasonably small number of iterations, punchable into your trusty hand calculator.

Problem 2.7
(a)
The easiest way is to use the method of images. The Green's function is simply the potential of a point charge
of 4 p e0 in empty space (here the z ¥ 0 volume) that satisfies the specified boundary conditions (here G§z=0 = 0 for a
Dirichlet problem), so we imagine a charge at (in cylindrical coordinates) x” £ = Hv£ , f£ , z£ L and place an image charge
at x” ≥ = Hv≥ , f≥ , z≥ L. The system is invariant under rotation about the z£ -axis, so we expect the image charge to be on
the z£ -axis as well (of course we're only allowed to put it below the plane). In fact the image should be exactly the
reflection of the point charge about the x -y plane with opposite charge — the lines of force will be perpendicular to
the z = 0 plane only if the placement of charges is symmetric about said plane. So we guess x” ≥ = Hv£ , f£ , -z£ L:
1
1
1
1
÷”, ÷x”£ L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
GHx
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ`ÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÷x”ÅÅÅÅ£ Å§Å - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÷x”ÅÅÅÅ≥ÅÅÅÅ§ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷
÷
÷÷
÷

÷÷
÷

÷÷
÷

£
£
£
†v - v + Hz - z L z§
†v - v + Hz + z£ L z` §

We see immediately that at z = 0 this gives zero as required.

÷” n-2
Hb x - c” ÿ x` L which we computed in problem 2.2, with x” Ø z£ z` . In the
(b)
We'll use ∑†b x” - c”§n ê ∑ x = n b °x” - b•
language of equation 1.44, r = 0 everywhere since there is no free charge distribution and F§z£ =0,v£ <a = V ,
F§z£ =0,v£ >a = 0. Remember that n£ is the outward pointing normal so n` £ = -z` and we will incur an overall minus sign.

7
2p
a
V
∑G
÷”L = + ÅÅÅÅ1ÅÅÅÅÅÅ
÷”£ ∑G £
FHx
f£ ‡ v£ v£ ÅÅÅÅÅÅÅÅÅÅÅÅ
® FHx L ÅÅÅÅÅÅÅÅÅ£ÅÅÅ a = ÅÅÅÅÅÅÅÅÅÅ ‡
4p S
∑z
4p 0

0
÷÷
÷

÷÷
÷

£ L ÿ z` + z + z£
£
z
Hv
v
∑G
` ÿ z` = 0
÷÷÷” - ÷÷v
÷”£ L ÿ z` + z - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ ì v
ÅÅÅÅÅÅÅÅÅÅÅÅ = -H-1L Hv
÷÷÷” - ÷÷v
÷”£ + Hz
÷÷÷” - ÷÷v
÷”£ + Hz
∑ z£
- z£ L z` §3
+ z£ L z` §3
†v
†v
∑ G ƒƒ
2z
ÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷
÷
÷÷
÷”£ + ”zÅÅÅÅ§Å3ÅÅÅÅ

£
£
∑ z ƒz =0
†v - v
2p
a

Vz
÷”L = ÅÅÅÅ
FHx
ÅÅÅÅÅÅ ‡
f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷÷” - ÷÷v
÷”£ + ”zÅÅÅÅ§Å3ÅÅÅÅ
2p 0
0
†v

(c)
2p
a
2p
a
Vz

Vz
£
£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å
ÅÅÅ
Å
ÅÅÅ
=
ÅÅÅÅ
Å
ÅÅÅ
Å
Å
f
v
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
FHz”L = ÅÅÅÅÅÅÅÅÅÅ ‡

÷÷÷”£ + ”z§3
2p 0
2p 0
0
0
†-v
@Hv£ L2 + z2 D3ê2
ÄÅ
ÉÑa
ÅÅ
ÑÑ
-1
z
1
1y
y
i
i
ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ = V z jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ zzzz
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ + ÅÅÅÅÅ zzzz = V jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
= V z ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
!
!!!!!!
!
!!!!!!
è!!!!!!!!
è!!!!!!!!
1ê2
ÅÅÇ @Hv£ L2 + z2 D ÑÑÖ
z{
a2 + z2
a2 + z2 {
k
k
0

(d)

÷÷÷” - v
÷÷÷”£ + ”z§2 = ÷÷÷” ÷÷÷”£ ” ÷÷÷” ÷÷÷”£ ”
÷÷÷” - v
÷÷÷”£ L ÿ Hv
÷÷÷” - v
÷÷÷”£ L + z2 = v2 - 2 v
÷÷÷” ÿ v
÷÷÷”£ + Hv£ L2 + z2
†v
Hv - v + zL ÿ Hv - v + zL = Hv
÷÷÷” ÿ v
÷÷÷”£ y
i
Hv£ L2 - 2 v
= Iv2 + z2 M jjjj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz
v2 + z2
{
k

÷÷÷” ÿ v
÷÷÷”£ D ê Hv2 + z2 L ` 1 and we may expand the above (and
Within the range of integration v£ § a, so @Hv£ L2 - 2 v
powers thereof) using the binomial expansion

GHn + 1L
i n + k - 1 yz
iny
z H¡ xLk , †x§ < 1 and n > 0 , jj zz ª ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
H1 ≤ xL-n = ‚ jj
k
m{
GHm
+
1L
GHn - m + 1L
{
k
k
k=0
2p
a

Vz
÷”L = ÅÅÅÅ
FHx
ÅÅÅÅÅÅ ‡
f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p 0
0
Hv2 + z2 L3ê2

÷÷÷” ÿ v
÷÷÷”£ y-3ê2
ij
Hv£ L2 - 2 v
jj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅ zzzz
j
v2 + z2
k
{

£
£
£ 2
2p
a

Vz
i -3 ê 2 + k - 1 zy ijj 2 v v cosHf - f L - Hv L yzz
z jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
= ÅÅÅÅÅÅÅÅÅÅ ‡
f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ jj
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
3ê2
2
2
k
2p 0
v +z
{k
k
0
Hv2 + z2 L
{

k=0

k

Note that Ÿ02 p f£ cosn Hf - f£ L to any odd n is zero because the integrand is odd. Also Ÿ02 p f£ cos2 Hf - f£ L = p. So
ÅÄÅ
2p
a
ÅÅ
3 2 v v£ cosHf - f£ L - Hv£ L2

Vz
÷”L = ÅÅÅÅ
FHx
ÅÅÅÅÅÅ ‡
f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ1 + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
3ê2
2
2p 0
v2 + z2
0
Hv2 + z2 L ÅÅÇ
ÉÑ
2
ÑÑ
15 ij 2 v v£ cosHf - f£ L - Hv£ L2 yz
Ñ
j
z
+ ÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + …ÑÑÑÑ
ÑÑ
8 k
v2 + z2
{
Ö
2
£
£
a
i
y
Vz
3
2
p
Hv
v
L
15
4 v2 Hv£ L2 p + 2 p Hv£ L4
j
= ÅÅÅÅÅÅÅÅÅÅ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj2 p - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
4
3ê2
2 + z2
2
2
2
2
2p 0
2
v
8
Hv + z L
Hv + z L
k
{
ij a2
y
a4 ê 4
15 4 v2 a4 ê 4 + 2 a6 ê 6
jj2 ÅÅÅÅÅÅÅÅÅ - 3 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
j
4
2
2
v +z
8
Hv2 + z2 L
k 2
{
2
2
2
2
i
y
Va
z
5 3 v a + a4
3
a
j
z
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzz
2 Hv2 + z2 L3ê2 k
8 Hv2 + z2 L4
4 v2 + z2
{

Vz
1
= ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2 Hv2 + z2 L3ê2

8

Both results in (c) and (d) share the common range v = 0, z p a. Plugging this in to the last expression:
V a2
FHz”L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

z
ÅÅÅÅÅÅÅÅ
z3

ij
y
3 a2
5 a4
V a2
jj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzz = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j
z
2
4
4 z
8 z
2
k
{

1
ÅÅÅÅÅÅÅÅ
z2

ij
y
3 a2
5 a4
jj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzz
j
z
2
4
4 z
8 z
k
{

Expanding the result in (c) in orders of a ê z gives the same thing (of course!):

ij
yz
ÄÅ
É
1 a 2 3 a 4
1
5 a 6
jj
zz
y
3 a2
V a2 i
5 a4
Å
i
yÑÑ
FHz”L = V jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz = V ÅÅÅÅ1 - jj1 + ÅÅÅÅÅ J ÅÅÅÅÅ N + ÅÅÅÅÅ J ÅÅÅÅÅ N + ÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅ N + …zzÑÑÑÑ = ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjjj1 + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzzz
2
2
4
ÅÇ
"#####################2#
2 z
8 z
16 z
k
{ÑÖ
4
2
z
z
8
z
k
{
1 + Ha ê zL {
k